2003
DOI: 10.1021/es034455a
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Populations Associated with the Oxidation and Reduction of Arsenic in an Unsaturated Soil

Abstract: Microbial populations responsible for the oxidation and reduction of As were examined in unsaturated (aerobic) soil columns treated with 75 microM arsenite [As(III)] or 250 microM arsenate [As(V)]. Arsenite [As(III)] was rapidly oxidized to As(V) via microbial activity, whereas no apparent reduction of As(V) was observed in the column experiments. Eight aerobic heterotrophic bacteria with varying As redox phenotypes were isolated from the same columns. Three isolates, identified as Agrobacterium tumefaciens-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
165
0
9

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(186 citation statements)
references
References 43 publications
12
165
0
9
Order By: Relevance
“…3c). Both As(V) and As(III) are mainly sequestered by iron minerals (Macur et al 2004;Islam et al 2005), and the adsorption and desorption of As from the minerals determines the mobility of As in the soil (Smedley and Kinniburgh 2002). Dissolved organic matter could compete with As for adsorption sites at mineral surface, decrease As(V) and As(III) adsorption and enhanced As release to the soil solution in the paddy soil Williams et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…3c). Both As(V) and As(III) are mainly sequestered by iron minerals (Macur et al 2004;Islam et al 2005), and the adsorption and desorption of As from the minerals determines the mobility of As in the soil (Smedley and Kinniburgh 2002). Dissolved organic matter could compete with As for adsorption sites at mineral surface, decrease As(V) and As(III) adsorption and enhanced As release to the soil solution in the paddy soil Williams et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent follow-up characterizations of this organism and this process failed to materialize; however, approximately 2 decades later, Santini et al (52) described the isolation and initial characterization of a Rhizobiumlike bacterium (strain NT-26) that could grow chemolithoautotrophically with As III as a sole electron donor for energy generation and with CO 2 as a sole carbon source. Soon thereafter, and in part stimulated by the massive arsenic poisoning disaster in Bangladesh (2), a series of studies initiated the characterization of microbial As III oxidation in natural environments, including geothermal springs (9,11,12,17,19,24,25,35,51) and soils (41); in mining-contaminated environments (6,13,40); and, most recently, in anoxic photosynthesis (21,33 (28,31) indicated the role and importance of the sensor kinase AioS and its putative regulatory partner AioR (a bacterial enhancer binding protein), direct proof of these two proteins working together as part of a putative As III signal perception and transduction cascade was just recently provided by Sardiwal et al (54), who demonstrated the autophosphorylation of an AioS component and the AioS-specific phosphorylation of AioR. Recently, our work has expanded this regulatory model to now include a third component, AioX, which is a periplasmic As III binding protein that is also essential for aioBA expression (39 …”
mentioning
confidence: 99%
“…were As(V) reducing bacteria isolated in aerobic conditions. Rates of As(V) reduction by those strains ranged from 0.5 to 3.3 μmol/(L·day) per 10 9 cells Macur et al, 2004). In our study, the reduction rate for HN-2 was 0.66 μmol/(L·hr) with initial cell density of 10 7 CFU/mL.…”
Section: As(iii)-oxidizing Bacteriamentioning
confidence: 45%
“…Universal eubacterial primers (27F:5′-AGAGTTTGATCCTGGCTCAG-3′;1492R:5′-GGYT ACCTTGTTACGACTT-3′) (Lane, 1991) targeting 16S rRNA gene and primers (F:5′-GTSGGBTGYGGMTAYCABGYCTA-3′; R:5′-TTG TASGCBGGNCGRTTRTGRAT-3′) targeting aroA gene (Inskeep et al, 2007) were used for PCR. The occurrence of arsenate reductase gene arsC in the isolated strain was investigated using five reported primers (Bachate et al, 2009;Chang et al, 2008;Macur et al, 2004;Macy et al, 2000;Sun et al, 2004). The PCR products were checked using 1.0% agarose gel electrophoresis and sequenced.…”
Section: Pcr Amplification Of 16s Rdna Aroa Gene and Arsc Genementioning
confidence: 99%